Effect of Lactobacillus plantarum 'KR107070' and a propionic acid‐based preservative on the fermentation characteristics, nutritive value and aerobic stability of alfalfa‐corn mixed silage ensiled with four ratios. (30th October 2017) - Wang, Musen; Yu, Zhu; Wu, Zhe; Hannaway, David B.
Abstract: The effect of Lactobacillus plantarum 'KR107070' and a propionic acid‐based preservative on the quality and aerobic stability of alfalfa‐corn mixed silage ensiled with four ratios was evaluated. A 4 × 4 factorial arrangement was used in a completely randomized design in this study. The chopped alfalfa and corn were made into four alfalfa to corn ratios (containing 20, 40, 60 and 80% corn), each of which was treated with (i) distilled water; (ii) 1 × 10 6 colony forming units per g of L. plantarum 'KR107070'; (iii) a chemical additive consisting of 0.24% propionic acid, 0.24% sodium propionate and 0.18% formic acid; (iv) a combination of (ii) and (iii). Treated forages mixture was ensiled with triplicate in a 5‐L polythene bucket for 180 days. At silo opening, the fermentation characteristics of silage were enhanced with a lower pH value, higher lactic acid content and lower ammoniacal nitrogen concentration and its relative feed value decreased, with a higher ratio of corn for all treatments. The application of a chemical additive alone, or in combination with L. plantarum 'KR107070', decreased ammoniacal nitrogen concentrations and increased water soluble carbohydrates contents than control or L. plantarum 'KR107070' for each silage of four ratios, in addition to enhancing the aerobic stability of 60 and 80% corn silages compared to L. plantarum 'KR107070'. The 60% corn silage, treated with combining 0.24% propionic acid, 0.24% sodium propionate and 0.18% formic acid with L. plantarum 'KR107070', is better in terms of conservation quality and aerobic stability.